2009
DOI: 10.1128/aac.00680-08
|View full text |Cite
|
Sign up to set email alerts
|

The Electricidal Effect: Reduction of Staphylococcus and Pseudomonas Biofilms by Prolonged Exposure to Low-Intensity Electrical Current

Abstract: The activity of electrical current against planktonic bacteria has previously been demonstrated. The shortterm exposure of the bacteria in biofilms to electrical current in the absence of antimicrobials has been shown to have no substantial effect; however, longer-term exposure has not been studied. A previously described in vitro model was used to determine the effect of prolonged exposure (i.e., up to 7 days) to low-intensity (i.e., 20-, 200-, and 2,000-microampere) electrical direct currents on Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 38 publications
4
117
2
Order By: Relevance
“…Additionally, up to 5-log reductions in Pseudomonas aeruginosa biofilms were observed after 7 days leading to the assertion that long-term exposure to low-intensity current has a notable effect of reducing the numbers of viable CFUs for staphylococcal and pseudomonal biofilms (the electricidal effect). The experiment also demonstrated that higher levels of treatment current and/or longer treatment periods yielded greater reductions in viable biofilm bacteria [82].…”
Section: The Electricidal Effectmentioning
confidence: 77%
See 2 more Smart Citations
“…Additionally, up to 5-log reductions in Pseudomonas aeruginosa biofilms were observed after 7 days leading to the assertion that long-term exposure to low-intensity current has a notable effect of reducing the numbers of viable CFUs for staphylococcal and pseudomonal biofilms (the electricidal effect). The experiment also demonstrated that higher levels of treatment current and/or longer treatment periods yielded greater reductions in viable biofilm bacteria [82].…”
Section: The Electricidal Effectmentioning
confidence: 77%
“…To date, there has been no definitive explanation for the mechanism of electrically induced reductions The most recent and significant advances in the field include the discovery of the "electricidal effect", a long-term reduction in the viability of biofilms using DC electric current without antimicrobials [82,83]. There should be no doubt that del Pozo's recent findings regarding the electricidal effect contribute significant advancements to the therapeutic strategy of electrical bacterial control.…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…This community of bacterial cells, embedded in a matrix of extracellular polymeric substance and attached to the foreign body surface, is characterized by high resistance to antibiotics and host defense mechanisms [1,11]. Application of electric current has been shown in vitro to have a direct adverse effect on bacterial biofilms, reducing the number of viable bacteria in a time-dependent and dose-dependent manner [3]. Animal models of implant-associated infections have confirmed the action of electric current against biofilm cells [4,5].…”
mentioning
confidence: 99%
“…When applied to instrumentation in vitro, small electric currents are able to detach biofilm [5,6]. As a result, the bacteria are rendered more susceptible to antibiotics.…”
Section: Introductionmentioning
confidence: 99%